The Olympus Scandal: a documentary investigation inside a major Corporate Governance Scandal in Japan. - Sadet, Fabien (2013)
Purpose / Research Problem – This dissertation aims at investigating the Corporate Governance scandal that occurred at Olympus Corporation in 2011. Drawing from its analysis and conclusions, the study arrives to a set of factors influencing such a scandal, such as corporate culture and poor Corporate Governance design. The research has not yet fully explored this scandal, although it appears important in order to enhance Corporate Governance designs around the world.